Direct synthesis of nanocrystalline silver from the reaction between silver carboxylates and n-trioctylphosphine - Charan, Shobhit; Singh, Narendra; Khanna, P. K.; Patil, K. R. (Journal of Nanoscience and Nanotechnology, 2006)
Neat n-Trioctylphosphine (TOP) has been used for the first ever time for reduction of silver nitrate and silver carboxylates (citrate, oleate, and myristate) under mild thermal reaction conditions. UV-visible absorption measurements of re-dispersible silver particles that were obtained by reduction of silver myristrate (product-IV) and silver nitrate (product-I) showed surface plasmon resonance absorption peak at 400 nm. The powder XRD pattern of fcc zero-valent silver resulted in diameters in the range of about 25-30 nm. TEM analysis showed particle diameter similar to that was observed by the XRD. FTIR spectroscopy revealed that the organics from the carboxylate group are retained by the nano-particles in case of product-IV however, presence of TOP is observed in product-I. It is found that when silver nitrate is reduced by TOP, spherical silver nano-particles with poor redispersity are formed but extended heating results in formation of long silver rods of micrometer size however, the re-dispersible nano-particles are easily formed when silver carboxylates are reduced by TOP.
Keywords: Chemical synthesis; Nanocrystalline; noble metal; XRD

One-step preparation of nanosized Ag-PdCo-powder and its alloy formation at low temperature - Khanna, P. K.; Singh, N.; Kulkarni, D.; Marimuthu, R.; Charan, Shobhit; Patil, K. R.; Jain, G. H. (Synthesis and Reactivity in Inorganic Metal-Organic and Nano-Metal Chemistry, 2007)
Nano-sized silver-palladium co-powder has been synthesized from silver nitrate-palladium chloride by wet chemical method. The present experimental conditions are applied for the first time for Ag-Pd co-powders wherein sodium formaldehyde sulfoxylate (SFS) has been used as an external reducing agent to simultaneously reduce respective metal salts. SFS reduces the metal salts at room temperature thus prevents formation of bigger particles of the respective metals in co-powder. Powder X-ray diffraction measurements ( XRD) and Transmission electron microscopy ( TEM) suggest the formation of nano-sized Ag-Pd co-powder with particle diameter in the range of about 25 nm. SEM shows that the powder morphology changes with temperature. Heat treatment of 90: 10 (Ag:Pd) composition showed shift in XRD peaks indicating alloy formation of Ag/Pd at lower temperature. Thick-films generated by use of the co-powder resulted in Ag/Pd alloy at about 500 degrees C as confirmed by the XRD. Thermal analysis showed that Ag/Pd co-powders initially gain the weight due to oxidation followed by the weight loss.
Keywords: alloy; Chemical synthesis; nano-powder; noble metal; Transition Metal